Factor of farmer shifting in varieties of coconut production / Mohd Asri Syafiq Ashaari - Syafiq Ashaari, Mohd Asri (Faculty of Plantation and Agrotechnology, 2015)
The research was carried out to determine the factor of farmer shifting in varieties of coconut production. This study was conducted at Muar, Johor for 4 months. The determination of the factor was classified into three independent factors which there are demographic, attitude and market factor which respond to dependent factor which is farmer shifting in variety and was used six parameters to identify the factor. This study also used interview the farmer and questionnaire to carry out the survey. About 150 coconut farmers were interview and fill questionnaire form at Muar, Johor. The questionnaire was design in 19 questions which 12 question for independent factor, 3 questions for dependent factor and 4 questions for socio profile of farmers. The 5 questions under demographic factor, 4 questions under attitude factor, 3 questions under market factor, and 3 questions for dependent factor. Result of the study showed that the market factor was significant to farmer shifting in variety of coconut production because there had high demand of new variety in the market and high price in current market. For the demographic factor, there is no influence the farmer to shift in the current variety to new variety. This is because most farmers are not frequent to extension program indirectly slow to use the extension service in their coconut production activity. This will make the farmers not gain new information about a certain variety, so this will indicate that demographic factor does not influence the shifting in variety among coconut farmers. For the attitude factor, the result show attitude factor does not influence farmers to shift from current variety to new variety because the incentive provide by the government still cannot support them to shifting from current variety to new variety. The result also showed that the market factor as a domain factor which influence the farmer shifting in varieties in coconut production.